Comparison of biofilms morphology for two strains of marine sulfate-reducing bacteria using atomic force microscopy - Nawawi, M.F.; Sahrani, F.K.; Usup, G.; Ahmad, A.; Wan Muda, W.M.L. (University Kebangsaan Malaysia, 2013)
AISI 304 stainless steel coupons were immersed in VMNI medium containing two strains of Sulfate-reducing bacteria which were isolated from Port Dickson, Negeri Sembilan. The immersion period were set for twenty-four hour, seven days, nine days and fifteen days. At the end of each period, the biofilm were formed on the surface will be maps using Atomic Force Microscopy. The image were taken using contact mode in the 70 μm x 70 μm and 10 μm x 10 μm resolution. Bacteria counts were done using the dilution and plate count technique. Image showed that SRB2 contain more bacteria cell attached to the metal surface by the 7th day of immersion compare to SRB1. But SRB1 produce more condensed and slime like biofilm with some crystallization precipitation while SRB2 bacteria cell were loosely attached. SRB1 bacteria cell were engulf in the slime like matrix while SRB2 bacteria cell is densely packed together. SRB2 showed a slightly higher rate growth in the medium compared to SRB1 but produce low amount of biofilm matrix while SRB1 produce a lot of bio-matrix precipitation and slime formation.